2019
DOI: 10.17776/csj.403516
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of Road Traffic Signs by Various Road Users in Kano City

Abstract: Human perception of the information on the road signs is a critical factor in determining the safe use of both the vehicle and the interacting environment. A total of 30 road traffic signs which includes10-warning, 10-regulatory and 10-informatory signs were evaluated using 190 questionnaires to determine comprehension level of road users in Kano. The questionnaire was administered to both private and commercial drivers of trucks, cars, tricycle, motorcycle, and bicycle. Majority of the respondents are male (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…The results show that 63.1% and 36.9% of the respondents are male and female, respectively. These results corroborate the prior findings of Makinde and Opeyemi [2], Adedeji et al [9] and Umar and Bashir [5], who found that the majority of research participants were male.…”
Section: Characteristics Of Respondentssupporting
confidence: 92%
See 1 more Smart Citation
“…The results show that 63.1% and 36.9% of the respondents are male and female, respectively. These results corroborate the prior findings of Makinde and Opeyemi [2], Adedeji et al [9] and Umar and Bashir [5], who found that the majority of research participants were male.…”
Section: Characteristics Of Respondentssupporting
confidence: 92%
“…To a large extent, a driver's ability to interpret traffic control devices is determined by his or her own individual traits; in particular, the driver's level of education plays a significant role in this regard. [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…For the case of the female, road marking, warning signs, informative signs, and regulatory signs were understood by 32, 27, 48, 35 females, respectively. The male gender understands the traffic signs compared to the female which is in agreement to previous findings of Umar and Bashir [8].…”
Section: Drivers Factor By Gendersupporting
confidence: 91%
“…In Turkey, participants correctly identified 81% of the signs presented [13]. In Kano city, Nigeria, it was found that the average traffic sign comprehension level was as high as 79% [14]. A study of drivers' sign comprehension across four countries (Poland, Finland, Canada and Israel) found that on average the drivers only identified 58.5% of the signs correctly [5].…”
Section: Discussionmentioning
confidence: 99%
“…In Kano city, Nigeria, it was found that the average traffic sign comprehension level was as high as 79%, with the least comprehension being 54.7% on the "Park and Ride" sign. However, they found that truck drivers had a lower understanding level than all other classes of road users [14]. A study of drivers' sign comprehension across four countries (Poland, Finland, Canada and Israel) found that on average the drivers identified 58.5% of the signs correctly [5].…”
Section: Introductionmentioning
confidence: 99%